(untitled) (Archive of Conferences, 2021)
In this article, the author envisages further development and improvement of social protection of young people, development of organizational and material means of distinguishing their talents among schoolchildren, young students and students studying in higher and secondary vocational colleges. It is based on the fact that the phenomenon of competition in all spheres of human life has entered, from the day of the birth of a person, the obligation to compete with himself and others like him